Drone fly, rat-tailed maggot Eristalis tenax (Linnaeus) (Insecta: Diptera: Syrphidae) - Margaret Pfiester; Phillip E. Kaufman (EDIS)
EENY-445, a 6-page illustrated fact sheet by Margaret Pfiester and Phillip E. Kaufman, is part of the Featured Creatures collection. It describes this hover fly that mimics the European honey bee and is adapted to living in polluted habitats — its distribution, description, life cycle, economic importance, and management. Includes references. Published by the UF Department of Entomology and Nematology, March 2009.